Cancer statistics for African Americans, 2019 - DeSantis, Carol E.; Miller, Kimberly D.; Goding Sauer, Ann; Jemal, Ahmedin; Siegel, Rebecca L. (CA: a cancer journal for clinicians, 2019)
In the United States, African American/black individuals bear a disproportionate share of the cancer burden, having the highest death rate and the lowest survival rate of any racial or ethnic group for most cancers. To monitor progress in reducing these inequalities, every 3 years the American Cancer Society provides the estimated number of new cancer cases and deaths for blacks in the United States and the most recent data on cancer incidence, mortality, survival, screening, and risk factors using data from the National Cancer Institute, the North American Association of Central Cancer Registries, and the National Center for Health Statistics. In 2019, approximately 202,260 new cases of cancer and 73,030 cancer deaths are expected to occur among blacks in the United States. During 2006 through 2015, the overall cancer incidence rate decreased faster in black men than in white men (2.4% vs 1.7% per year), largely due to the more rapid decline in lung cancer. In contrast, the overall cancer incidence rate was stable in black women (compared with a slight increase in white women), reflecting increasing rates for cancers of the breast, uterine corpus, and pancreas juxtaposed with declining trends for cancers of the lung and colorectum. Overall cancer death rates declined faster in blacks than whites among both males (2.6% vs 1.6% per year) and females (1.5% vs 1.3% per year), largely driven by greater declines for cancers of the lung, colorectum, and prostate. Consequently, the excess risk of overall cancer death in blacks compared with whites dropped from 47% in 1990 to 19% in 2016 in men and from 19% in 1990 to 13% in 2016 in women. Moreover, the black‐white cancer disparity has been nearly eliminated in men <50 years and women ≥70 years. Twenty‐five years of continuous declines in the cancer death rate among black individuals translates to more than 462,000 fewer cancer deaths. Continued progress in reducing disparities will require expanding access to high‐quality prevention, early detection, and treatment for all Americans.